A design of a fixed bed plasma DRIFTS cell for studying the NTP-assisted heterogeneously catalysed reactions. Issue 5 (4th February 2020) - Stere, Cristina; Chansai, Sarayute; Gholami, Rahman; Wangkawong, Kanlayawat; Singhania, Amit; Goguet, Alexandre; Inceesungvorn, Burapat; Hardacre, Christopher
Abstract : A newly developed DRIFTS cell for the in situ study of non-thermal plasma-assisted heterogeneously catalysed reactions is presented and evaluated using methane oxidation over a Pd/Al2 O3 catalyst. Abstract : A newly developed diffuse reflectance infra-red Fourier transform spectroscopy (DRIFTS) cell for the in situ study of non-thermal plasma (NTP)-assisted heterogeneously catalysed reactions is presented and evaluated using methane oxidation over a Pd/Al2 O3 catalyst. By using the new fixed bed plasma DRIFTS cell coupled with mass spectrometry, the NTP discharge is generated inside the catalyst bed and allows simultaneous, in situ DRIFTS analysis to be undertaken. The spectroscopy has revealed that the formation of surface species, e.g. formate and carbonate, is significantly influenced by NTP generation under methane oxidation conditions at different voltages when comparing with the conventionally thermal activation. During the NTP-DRIFTS-MS measurements, it is also found that there is no signal interference between IR beam and plasma plume, making this a viable DRIFTS system for studying the plasma catalysis.